Efektivitas Budaya Literasi dalam Meningkatkan Keterampilan 4C Siswa UPT SD Negeri 060871 Medan - Dicky Chandra Lubis; Fadillah Annisa; Hilda Melani Purba; Nurhaliza Ertays Siregar; Safran Hasibuan (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research aims to find out how literacy culture influences the 4C skills of elementary school students. This research uses qualitative research methods with a descriptive approach. The descriptive method is a problem solving procedure by describing the condition of the subject or object of research based on facts that are seen as they really are. The data collection technique uses observation and interview techniques. The research results show that the implementation of literacy culture that has been implemented or carried out is quite effective. From the literacy culture implemented, students have begun to have quite good 4C skills, namely Communication, Collaboration, Critical Thinking, and Creativity and Innovation.